Sub threshold analog &RF parameter extraction of graded channel gate stack DG-MOSFETs with high K material using NQS approach - Swain, Sanjit Kumar; Adak, Sarosij; Parija, Saradiya; Sarkar, Chandan Kumar (2017 Devices for Integrated Circuit (DevIC), 2017)
In this paper we study the analog performance and also extract the RF parameters of Graded channel Gate stack (GCGS) DG MOSFET structure for different high K materials. A relative assessment was also carried out by using 2D Sentrausu TCAD simulator for different high-K oxide layers. This novel device can be one of the promising alternatives to the existing devices for future high speed switching and low power circuit applications. It has several advantages such as reducing leakage current, getting higher breakdown voltage, reduced bipolar parasitic effects and improved frequency response. The given device must be investigated with respect to different doping profile and high K materials to have better reliability. Non-quasi-static (NQS) effect was also considered to extract the RF parameters for a given graded doping profile across the channel for different high-K materials. The result evident that variation of high K oxide materials with respect to high-low doping profile across the channel gives useful information's on the analog and RF performance of the proposed device.